Conflict, Traditional, and Family Resistance: The Pattern of Dispute Resolution in Acehnese Community According to Islamic Law - Djawas, Mursyid; Abdul Samad, Sri Astuti (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
This study discusses the resolution of disputes through adat and family security in Acehnese society according to Islamic law. The problems examined are the pattern of resolving family conflicts through adat mechanisms in Aceh; The relationship between resolving conflicts through adat and family resilience in Aceh and a review of Islamic law towards resolving family conflicts through adat in Aceh. This study uses a qualitative approach, which is to explain, describe, and analyze in-depth the results of research. Data collection techniques used were literature study and interviews with informants. While the data were analyzed using Islamic legal theory and traditional law. This research concludes that there are several patterns for example involving various parties such as Jurong, Keuchik, Tuha Peut, Teungku Imum, Imum Mukim, and the place of dispute resolution at meunasah sometimes at Keuchik's house. There is a close relationship between resolving disputes through adat and family resilience, meaning that many family problems that are resolved through adat mechanisms do not go through formal legal avenues. Then the dispute resolution is in line with Islamic law which is included in the urf category with a review of the benefits.